Controlling the Layer Thickness of Zinc Oxide Photoanode and the Dye-Soaking Time for an Optimal-Efficiency Dye-Sensitized Solar Cell - Magiswaran K.; Norizan M.N.; Mahmed N.; Mohamad I.S.; Idris S.N.; Sabri M.F.M.; Amin N.; Sandu A.V.; Vizureanu P.; Nabia?ek M.; Salleh M.A.A.M. (MDPI, 2024)
Dye-sensitized solar cells (DSSCs) were developed by exploiting the photovoltaic effect to convert solar energy into electrical energy. The photoanode layer thickness significantly affects the semiconductor films ability to carry electronic charges, adsorb sensitizing dye molecules, and lower the recombination of photo-excited electrons injected into the semiconductor. This study investigated the dependence of the zinc oxide (ZnO) photoanode thin-film thickness and the film soaking time in N719 dye on the photocurrentvoltage characteristics. The ZnO photoanode was applied to glass using the doctor blade method. The thickness was varied by changing the scotch tape layers. The ZnO-based DSSC attained an efficiency of 2.77% with three-layered photoanodes soaked in the dye for three hours, compared to a maximum efficiency of 0.68% that was achieved with three cycles using the dip-coating method in other research. The layer thickness of the ZnO photoanode and its optimal adsorption time for the dye are important parameters that determine the efficiency of the DSSC. Therefore, this work provides important insights to further improve the performance of DSSCs. 2022 by the authors.